2023
DOI: 10.3389/fonc.2023.1121485
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a CECT-based radiomics model for predicting IL1B expression and prognosis of head and neck squamous cell carcinoma

Abstract: IntroductionIt is necessary to explore a noninvasive method to stratify head and neck squamous cell carcinoma (HNSCC)’s prognosis and to seek new indicators for individualized precision treatment. As a vital inflammatory cytokine, IL1B might drive a new tumor subtype that could be reflected in overall survival (OS) and predicted using the radiomics method.MethodsA total of 139 patients with RNA-Seq data from The Cancer Genome Atlas (TCGA) and matched CECT data from The Cancer Image Archive (TCIA) were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Texture features were derived from analyzing the relative spatial distribution and intensity levels of voxels to characterize the structural texture of two-dimensional or three-dimensional images [ 33 ]. Numerous studies have demonstrated that texture features provide valuable insights into tumor differentiation, pathological typing, radiogenomics, prognostic prediction, and more, as they reflect structural texture differences in intratumoral tissue anatomy [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Texture features were derived from analyzing the relative spatial distribution and intensity levels of voxels to characterize the structural texture of two-dimensional or three-dimensional images [ 33 ]. Numerous studies have demonstrated that texture features provide valuable insights into tumor differentiation, pathological typing, radiogenomics, prognostic prediction, and more, as they reflect structural texture differences in intratumoral tissue anatomy [ 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, radiomics has emerged into basic and clinical medicine and has expanded our knowledge of the radiomic and functional characteristics of HNSCC. Several studies have shown that CT‐based radiomics can be used to diagnose, classify, and predict the prognosis of HNSCC 23,47 . Hence, CT‐based radiomics is suitable for assessing the heterogeneity of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that CT-based radiomics can be used to diagnose, classify, and predict the prognosis of HNSCC. 23,47 Hence, CT-based radiomics is suitable for assessing the heterogeneity of HNSCC.…”
Section: G U R Ementioning
confidence: 99%
See 2 more Smart Citations